Vacuolar transporter Avt4 is involved in excretion of basic amino acids from the vacuoles of Saccharomyces cerevisiae. Issue 6 (3rd June 2014) - Sekito, Takayuki; Chardwiriyapreecha, Soracom; Sugimoto, Naoko; Ishimoto, Masaya; Kawano-Kawada, Miyuki; Kakinuma, Yoshimi
Abstract: Basic amino acids (lysine, histidine and arginine) accumulated in Saccharomyces cerevisiae vacuoles should be mobilized to cytosolic nitrogen metabolism under starvation. We found that the decrease of vacuolar basic amino acids in response to nitrogen starvation was impaired by the deletion of AVT4 gene encoding a vacuolar transporter. In addition, overexpression of AVT4 reduced the accumulation of basic amino acids in vacuoles under nutrient-rich condition. In contrast to AVT4, the deletion and overexpression of AVT3, which encodes the closest homologue of Avt4p, did not affect the contents of vacuolar basic amino acids. Consistent with these, arginine uptake into vacuolar membrane vesicles was decreased by Avt4p-, but not by Avt3p-overproduction, whereas various neutral amino acids were excreted from vacuolar membrane vesicles in a manner dependent on either Avt4p or Avt3p. These results suggest that Avt4p is a vacuolar amino acid exporter involving in the recycling of basic amino acids. Graphical abstract: : In the budding yeast Saccharomyces cerevisiae, basic amino acids that are highly accumulated in vacuoles are extruded by vacuolar amino acid transporter Avt4.